Pteridaceae endémicas del Perú - León, Blanca (2006)
This family is recognized in Peru with 18 genera and more than 150 species (Tryon & Stolze, 1989b; Smith et al., 2005). Although the Pteridaceae is the most species rich family in the Peruvian flora, only eight species in four genera are recognized as endemics. All endemic species are terrestrial plants occupying open areas in the Desert Shrubland and Mesoandean regions, between 500 and 3500 m elevation. Only one taxon is found in a protected area.